A construção de material de formação continuada em ótica física para professores do ensino médio - Rodrigues Júnior, William Saraiva (2021)
The way in which physics education is presented in many schools shows that although changes have occurred over the last decades, very few aret the differences between the way physics was taught in the past and how it is today. Physics teaching remains focused on a theoretical and mathematical approach, with physical phenomena provided through a brief reading and the central focus concentrated on solving exercises and applying formulas. Some theorists, such as Piaget, Vygotsky and Bruner argue that the student’s interaction with the environment plays a great role in the development processes. A way to make students more active and enable them to participate of these processes should be the use of experiments in the classroom. However, there are several problems that prevent its use in the classroom, including: lack of experience with experiments, lack of materials, lack of practical and theoretical knowledge, small number of physics classes as well as several other factors. These difficulties are present in all areas of physics, including optics. The present dissertation arises from the need to solve, or partially mitigate, the problem of teacher training and how experiences can be used by teachers in their classes to make optics classes more dynamic and motivating. As a central theme of study, Physical Optics is approached with an educational product that presents teaching strategy, didactic sequence and experiments of interference, diffraction and polarization of light. The experiments involve Lloyd’s mirror; diffraction of light on a blade, on a hair and on a CD; Malus’s law and luminous intensity. A series of exercises on the different topics of Physical Optics is also provided in the Educational Product, thus complementing the themes presented in the experiments. As the final remark, the Educational Product was used in a state school in the state of Ceará, Brazil, and was analyzed together with some physics teachers.